Pelatihan Pembuatan Laporan Keuangan Menggunakan Aplikasi UKM Pada UMKM Kedai Khabita Jl. Meranti Sawah Lebar Kec. Ratu Agung, Kota Bengkulu - Zoniarti, Zoniarti; Nurzam, Nurzam; Wijaya, Ermi; Efendi, Bahman; Subhi, Ramadan; Tiansari, Urba; Sriwijaya, Adio (Jurnal Gotong Royong, 2025)
This financial report and recording aims to analyze and give an impression of the success of an MSME. This financial report aims to compile a recording method using the Accounting application which may be able to overcome the difficulties faced by the Kedai khabita business. The method used in this activity helps owners to understand more about the preparation of financial reports, the introduction of features on how to infut the SME Accounting application The service is carried out interactively to guide MSME owners in recognizing, downloading, and using the Teman Bisnis application, as well as providing guidance in recording transactions and producing informative financial reports. The Teman Bisnis application has been socialized, which certainly has a positive impact on MSME business management, facilitates access to financing, and helps in long-term business planning. The results of this report preparation training are expected to be a solution for owners to overcome obstacles in their business. With this exercise, the author can utilize technology so that it can be used in the Kedai khabila business. the SME Accounting application has been implemented by the owner in order to overcome the problems he faces, as well as to know the profit and loss information he faces accurately and the financial position of his business. With the results obtained through accounting applications, business owners make decisions to develop their business.